2011
DOI: 10.1007/s00436-011-2462-9
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma spp. in Swedish game animals

Abstract: Serum and blood samples from 36 game animals, shot during the hunting seasons 2007-2009, were collected and analyzed for the presence of Trypanosoma spp. by three methods; Isolation, PCR and serology. Only fisseped animals were included, four different ruminants and wild boar. Trypanosomes could be isolated from two of the animals, and eight had detectable parasite DNA. Seven animals had high titers of anti trypanosoma IgG antibodies. The two isolated strains, one from roe dear and one from European elk, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…This protozoan group is considered typical for wild and domestic ruminants in Europe ( Werszko et al, 2020 b , Werszko et al, 2020a ), which was also confirmed in our study. Megatrypanum trypanosomes have been detected in cattle and wild bovids in Belgium, Italy, Ireland and Spain ( Doherty et al, 1993 ; Verloo et al, 2000 ; Villa et al, 2008 ; Amato et al, 2019 ; Bittner et al, 2019 ) as well as in wild cervid species, including roe deer, fallow deer and red deer in Sweden, Germany and Austria ( Friedhoff et al, 1984 ; Hoffmann et al, 1984 ; Hinaidy, 1987 ; Garcia et al, 2011 ; Neumüller et al, 2012 ); however, little data exists about their occurrence in Eurasian moose ( Kingston et al, 1985 ; Neumüller et al, 2012 ). Megatrypanum trypanosomes are generally non-pathogenic, causing only subclinical infection ( Matsumoto et al, 2011 ; Magri et al, 2021 ), which might be one of the reasons for random detection of the parasite in some cervid species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protozoan group is considered typical for wild and domestic ruminants in Europe ( Werszko et al, 2020 b , Werszko et al, 2020a ), which was also confirmed in our study. Megatrypanum trypanosomes have been detected in cattle and wild bovids in Belgium, Italy, Ireland and Spain ( Doherty et al, 1993 ; Verloo et al, 2000 ; Villa et al, 2008 ; Amato et al, 2019 ; Bittner et al, 2019 ) as well as in wild cervid species, including roe deer, fallow deer and red deer in Sweden, Germany and Austria ( Friedhoff et al, 1984 ; Hoffmann et al, 1984 ; Hinaidy, 1987 ; Garcia et al, 2011 ; Neumüller et al, 2012 ); however, little data exists about their occurrence in Eurasian moose ( Kingston et al, 1985 ; Neumüller et al, 2012 ). Megatrypanum trypanosomes are generally non-pathogenic, causing only subclinical infection ( Matsumoto et al, 2011 ; Magri et al, 2021 ), which might be one of the reasons for random detection of the parasite in some cervid species.…”
Section: Discussionmentioning
confidence: 99%
“…However, very little is known about Trypanosoma spp. infection in moose ( Kingston et al, 1985 ; Neumüller et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, trypanosomes have been described in domestic and wild animal species, such as Trypanosoma lewisi in rats (Rattus norvegicus, Karbowiak et al, 2009), Trypanosoma pestanai in badgers (Meles meles) (Peirce and Neal, 1974) and in a dog (Dyachenko et al, 2017), Trypanosoma vespertilionis and Trypanosoma dionisi in bats (Pipistrellus pipistrellus, Linhart et al, 2020), Trypanosoma theileri and Trypanosoma melophagium in domestic and wild ruminants (Buscher and Friedhoff, 1984;Villa et al, 2008;Neumüller et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some Tabanidae species such as Tabanus bromius and Haematopota pluvialis are considered vectors of T. theileri infection in cattle, in Europe and also Sweden (Dirie, et al, 1990;Neumüller, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%